2021
DOI: 10.1016/j.ebr.2020.100422
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude of the community towards epilepsy in Northwest Ethiopia: A huge gap on knowledge and attitude of the community

Abstract: Highlights The knowledge of the community was poor and their attitudes were negative. Residency and training affect knowledge and attitude of the community. Emphasis should be given on determinants of poor knowledge and negative attitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…Our study suggested that women had a higher level of knowledge than men and there was a relationship between gender and public knowledge of epilepsy. The results of this study are supported by a previous study showing that men had poor knowledge of epilepsy, especially if they did not know someone with epilepsy [14]. Another supporting study is by Emine and Nuray (2017) which showed that there was a significant relationship between gender and knowledge [10].…”
Section: Resultssupporting
confidence: 83%
“…Our study suggested that women had a higher level of knowledge than men and there was a relationship between gender and public knowledge of epilepsy. The results of this study are supported by a previous study showing that men had poor knowledge of epilepsy, especially if they did not know someone with epilepsy [14]. Another supporting study is by Emine and Nuray (2017) which showed that there was a significant relationship between gender and knowledge [10].…”
Section: Resultssupporting
confidence: 83%
“…This study is based on the result of a previous research work, which showed that a greater number of communities in the northwest Ethiopia had poor knowledge and a negative attitude toward epilepsy ( 39 ). This study aimed to assess the first aid practice measures taken by the community in managing people with epileptic seizure episodes.…”
Section: Discussionmentioning
confidence: 99%
“…However, social stigma against a certain group can make them unable to accept themselves, putting their behaviors under the control of society [53]. In particular, social stigma experienced in childhood, when self-identity is not fully established, can act as a risk factor for children with epilepsy to form a negative self-concept and perceive life as unhappy [30,35,37,42,51,[54][55][56].…”
Section: Chnrmentioning
confidence: 99%